2021
DOI: 10.1155/2021/7697785
|View full text |Cite
|
Sign up to set email alerts
|

Material Basis and Mechanism of Chansu Injection for COVID-19 Treatment Based on Network Pharmacology and Molecular Docking Technology

Abstract: Purpose. The clinical efficacy of Chansu injection for COVID-19 treatment has been confirmed. Its mechanism of action remains unclear. We used network pharmacology and molecular docking technology to explore the potential material basis and mechanism of action of Chansu injection for COVID-19. Methods. The main components of Chansu injection were determined using HPLC. The PharmMapper, SwissTargetPrediction, SEA, and TCMID databases were used to screen for the active ingredients and therapeutic targets of Chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The study employed the SwissTargetPrediction database (http:// www.swiss targe tpred iction.ch/), PharmMapper database (http:// www.lilab -ecust.cn/pharm mappe r/), and SEA database (https:// sea.bkslab.org/), and integrated the target library of specnuezhenide. 15,16 Dermatitis-related disease targets were searched through the GeneCards database (https://www.genec ards.org) and OMIM database (https://www.omim.org/). 17 The target of specnuezhenide and the disease target were import into Venny2.1 (https:// bioin fogp.cnb.csic.es/tools/ venny/) to obtain the intersection.…”
Section: Network Pharmacology Analysismentioning
confidence: 99%
“…The study employed the SwissTargetPrediction database (http:// www.swiss targe tpred iction.ch/), PharmMapper database (http:// www.lilab -ecust.cn/pharm mappe r/), and SEA database (https:// sea.bkslab.org/), and integrated the target library of specnuezhenide. 15,16 Dermatitis-related disease targets were searched through the GeneCards database (https://www.genec ards.org) and OMIM database (https://www.omim.org/). 17 The target of specnuezhenide and the disease target were import into Venny2.1 (https:// bioin fogp.cnb.csic.es/tools/ venny/) to obtain the intersection.…”
Section: Network Pharmacology Analysismentioning
confidence: 99%
“…As indicated in Figure 2b, The protein-protein interaction (PPI) network was constructed, and its average degree value was 12.990. The target genes greater than twice the average degree value (≥26) were considered core targets (Xu et al, 2021), and 26 genes had parameters that met the above criteria, which might be the core targets for the treatment of ALI. Information on the 26 core targets is shown in Appendix 2.…”
Section: Ppi Network Analysismentioning
confidence: 99%
“…The main active ingredients in CS included bufalin, resibufogenin, and cinobufagin, which possessed strong antiviral effects (Qi et al, 2018;Zhan et al, 2020). The result of molecular docking indicated that bufalin had the highest binding efficiency to 3CL protease, transcription factor AP-1 (ACE2), RNAdependent RNA polymerase (RdRp), and spike protein and potentially suggested that CS had a good therapeutic effect on COVID-19 (Xu et al, 2021). The top eight compounds in HSBD were quercetin, baicalein, kaempferol, beta-sitosterol, stigmasterol, isorhamnetin, naringenin, and formononetin.…”
Section: Potential Mechanismmentioning
confidence: 99%